The challenges of sustained development : the role of socio-cultural factors in East-Central Europe - Adam, Frane (Budapest ; New York : Central European University Press, 2005)
How wide is the gap between the new democracies of East-Central Europe and the most developed European nations? How can it be narrowed? The book is trying to address these issues in a comprehensive way, taking into account not only economical but socio-cultural and political aspects of development.
Introduction : the point of departure -- Civilisational competence -- Social capital -- Cognitive mobilisation -- Quality of governance -- Entrepreneurial spirit -- Social cohesion -- The openness of societies -- Developmental performance -- Conclusion.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Europe, Central -- Social conditions -- 1989-; Europe, Eastern -- Social conditions -- 1989-; Social change -- Europe, Central; Social change -- Europe, Eastern; Sustainable development -- Europe, Central; Sustainable development -- Europe, Eastern; Europe, Central -- Economic conditions -- 1989-; Europe, Eastern -- Economic conditions -- 1989-; Social indicators -- Europe, Central; Social indicators -- Europe, Eastern; Changement social -- Europe de l'Est.; Changement social -- Europe centrale; Développement durable -- Europe centrale; Développement durable -- Europe de l'Est.; Indicateurs sociaux -- Europe centrale; Indicateurs sociaux -- Europe de l'Est.; Europe centrale -- Conditions sociales -- 1989-; Europe de l'Est -- Conditions sociales -- 1989-; Europe centrale -- Conditions économiques -- 1989-; Europe de l'Est -- Conditions économiques -- 1989-; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Sociology -- General; Economic history; Social change; Social conditions; Social indicators; Sustainable development; Central Europe; Eastern Europe; Since 1989